Readiness of Cultural and Historical Tourism Destinations on Morotai Island for Sustainable Tourism - Getsa Victory Lekatompessy; Heru Suheryadi; Yohanes Sulistyadi; Asmawi; Andy Noviadi (The Postgraduate School of Tourism Sahid Polytechnic, 2026)
Purpose: The purpose of this study is to analyze the extent of the readiness of Morotai Island's cultural tourism destinations, especially at the Museum Trikora and Army Dock Beach tourist attractions, in applying the principles of sustainable tourism. These two objects were chosen because the management and facilities at the location have not been optimally developed, despite having high historical value. Research Methods: This research uses a qualitative descriptive method, where data collection techniques are carried out through observation, interviews, and documentation. Result and discussion: The findings show that both Museum Trikora and Army Dock Beach are not fully prepared to implement sustainable tourism principles. Museum Trikora has damaged facilities and restricted activities, while Army Dock Beach lacks official management and adequate facilities. Community involvement and coordination among agencies are limited. Implication: From the results of observations in the field and by approaching five main aspects, namely management, infrastructure and facilities, community involvement, environmental and cultural preservation, as well as promotion and accessibility, it was found that the level of understanding and involvement of the community and managers towards the principles of sustainable tourism is still relatively low. This research concludes that improving management, active community involvement, and strengthening supporting facilities are important steps to realize a more sustainable cultural tourism destination.